Stripped Red Giants - Helium Core White Dwarf Progenitors and their sdB Siblings - Heber, Ulrich (2017)
Some gaps in the mosaic of binary star evolution have recently been filled by the discoveries of helium-core white dwarf progenitors (often called extremely low mass (ELM) white dwarfs) as stripped cores of first-giant branch objects. Two varieties can be distinguished. One class is made up by SB1 binaries, companions being white dwarfs as well. Another class, the so-called EL CVn stars, are composite spectrum binaries, with A-Type companions. Pulsating stars are found among both classes. A riddle is posed by the apparently single objects. There is a,one-to-one correspondence of the phenomena found for these new classes of star to those observed for sdB stars. In fact, standard evolutionary scenarios explain the origin of sdB stars as red giants that have been stripped close to the tip of first red giant branch. A subgroup of subluminous B stars can also be identified as stripped helium-cores of red giants. They form an extension of the ELM sequence to higher temperatures. Hence low mass white dwarfs of helium cores and sdB stars in binaries are close relatives in terms of stellar evolution.